IMPLEMENTASI KEBIJAKAN PENGEMBANGAN USAHA MIKRO, KECIL DAN MENENGAH (UMKM) DI DINAS KOPERASI DAN UMKM DI KABUPATEN KAMPAR - Indrawan, M. Syach; Riyanti, Ratna; Sutrisno, Hafiz (Pahlawan Tuanku Tambusai University, 2024)
The Kampar Regency Department of Cooperative Trade and Micro, Small and Medium Enterprises has an important role in developing MSME businesses. The purpose of writing this thesis: Firstly, to find out the implementation of MSME development policies, second, to find out what are the inhibiting factors in implementing MSME development policies, third, to find out efforts to resolve obstacles in implementing MSME development policies at the Kampar Regency Cooperatives and MSMEs. The type of research used in this research is juridical-sociological using descriptive research characteristics. The results of the research in this research are: Firstly, the Kampar Regency Trade, Cooperatives and UMKM Service, has actually carried out outreach to business actors and also often carries out communication simply to carry out promotions or exhibitions at regional, national or local levels for these business actors to maximize communication from both parties, the second inhibiting factor in empowering MSMEs is that there is still a lack of discipline in implementing development policies, especially in the Department of Trade, Cooperatives and MSMEs. Then, there are problems when arranging time for developing MSMEs, and a lack of funds for outreach to MSME players. In this case, technology is also an inhibiting factor in implementing MSME development policies. The efforts of the Kampar Regency government to deal with factors inhibiting the implementation of MSME development policies at the Department of Trade, Cooperatives and UMKM are by providing guidance to MSME actors, empowering MSMEs through aid funds to MSME actors, providing special assistance and training by the Department of Industry, Trade and Cooperatives. and UMK for MSME actors, the Kampar district regional government carries out marketing and promotion of MSME products. Keyword: Policy Implementation, Development, MSMEs